A campanha nacional de educandários gratuitos (CNEG) e a nova organização escolar : histórias e memórias da educação no município de Ibicaraí /BA - Assis, Daisy Laraine Moraes de (2005)
Education in the 50 s presented itself as a possibility as a solution for national problems, as well as a means to build up a democratic society. In those times, the National Campaign of Free Schools (CNEG) had reached a great level of development with the creation of Junior High schools that were spread all over the country, through the support of the public budget. Thus, this dissertation aims at studying the initial process of development of the educational system in Ibicarí (BA) based on the presence of CNEG there and on its relationship with the institutionalization of a new school organization in the municipality that had just achieved the status of being emancipated, dealing with facts and happenings considered relevant, with the objective of preserving the local memory and building new knowledge about the past, taking into account a broader understanding of the history of education in that region. In order to achieve such goals, the following procedures were conducted: analysis of studies related to History , memory , and education , besides the use of various kinds of sources such as pictures, personal reports, notes, articles, newspapers and magazines in an attempt to reach a level of understanding in regards to the political and educational actions performed by CNEG in the municipality of Ibicaraí in the 50 s. That was the moment of the establishment of the first nucleus of the Campaign in Bahia, in the municipality of Itabuna, in which the 14 de Agosto High School belonged.